The Effect of Postural Exercise Program For The Elderly On Increasing Muscle Mass At I-Fit Indonesia, Central Jakarta - Muhammad Abdan Al Farras; Qorry Armen Gemael; R. Retna Kinanti Dewi; Habibi Hadi Wijaya; Dany Aulia (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The research aims to prove the influence of the postural training program for the elderly on increasing muscle mass at I-Fit Indonesia, Central Jakarta. This type of research uses experiments with a quantitative approach. The research design uses one group pre-test-post-test design. This design has a pre-test and post-test so that the influence of treatment can be calculated by comparing the post-test and pre-test scores. The subjects of this research were 12 I-Fit Indonesian consumers. The sample was selected using a purposive sampling technique. The test instruments used in this research were Bioimpedance analysis (BIA) and Basal Metabolic Rate (BMR). Based on the data from the normality test using the Shapiro-Wilk test, a sig value of 0.05 was obtained, normally distributed. The homogeneity test obtained a sig value of 0.495. Hypothesis testing obtained a sig value of 0.007. So it can be concluded that providing a postural program to the elderly can increase muscle mass in the elderly.